The Impacts of Reduced Access to Abortion and Family Planning Services: Evidence from Texas - Stefanie Fischer; Heather Royer; Corey White (Institute of Labor Economics (IZA), 2017)
Between 2011 and 2014, Texas enacted three pieces of legislation that significantly reduced funding for family planning services and increased restrictions on abortion clinic operations. Together this legislation creates cross-county variation in access to abortion and family planning services, which we leverage to understand the impact of family planning and abortion clinic access on abortions, births, and contraceptive purchases. In-state abortions fell 20% and births rose 3% in counties that no longer had an abortion provider within 50 miles. Births increased 1% and contraceptive purchases rose 8% in counties without a publicly-funded family planning clinic within 25 miles.
Keywords: J13; I18; J08; J18; I38; 330; family planning; abortion; birth; contraception; reproductive; health